Mechanical Cycling Stability of Organic Thin Film Transistors on Shape Memory Polymers. (24th May 2013) - Avendano‐Bolivar, Adrian; Ware, Taylor; Arreaga‐Salas, David; Simon, Dustin; Voit, Walter
<x xml:space="preserve">Abstract</x> Organic thin film transistors on shape memory polymers are fabricated by full photolithography. Devices show high mobility (0.2 cm2 V−1 s−1) and close to zero threshold voltage (‐4.5 V) when characterized as fabricated. After 1, 10, and 100 deformation cycles and in a deformed, metastable shape memory transition state, changes in mobility and Vth are measured and indicate sustained device functionality. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>